2018
DOI: 10.1159/000488009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium Thiosulfate on Arterial Stiffness in End-Stage Renal Disease Patients Undergoing Chronic Hemodialysis (Sodium Thiosulfate-Hemodialysis Study): A Randomized Controlled Trial

Abstract: Background: Arterial stiffness (AS) and vascular calcification are significantly related to a high cardiovascular mortality risk in hemodialysis (HD) patients. Intravenous sodium thiosulfate (IV STS) can prevent and delay the vascular calcification progression in uremic states; however, the STS effect on AS has not been assessed. This study aimed to evaluate the STS efficacy on vascular calcification and AS in HD patients. Methods: Fifty HD patients with abnormal AS, as measured via the cardio-ankle vascular i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 32 publications
(33 reference statements)
0
22
1
Order By: Relevance
“…The ADRs are common in patients treated with intravenous STS for vascular calcification, calciphylaxis, and cisplatin-induced hearing loss [9,10,[13][14][15]. Djuric et al documented nausea and vomiting (30.4%) and metabolic acidosis (14%) while treating advanced CKD patients of vascular calcification with STS [10].…”
Section: Adverse Drug Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ADRs are common in patients treated with intravenous STS for vascular calcification, calciphylaxis, and cisplatin-induced hearing loss [9,10,[13][14][15]. Djuric et al documented nausea and vomiting (30.4%) and metabolic acidosis (14%) while treating advanced CKD patients of vascular calcification with STS [10].…”
Section: Adverse Drug Reactionmentioning
confidence: 99%
“…Sodium thiosulfate (STS), also called sodium hydrosulfite, is an inorganic agent with antioxidant and vasodilatory properties [9]. STS is indicated for the treatment of acute cyanide poisoning [10]; however, its use for off-label indication has also been reported, such as for calcific uremic arteriolopathy or calciphylaxis, coronary artery calcification [10][11][12][13][14], and cisplatin-induced hearing loss [9,15]. A recent retrospective study proposed the potential therapeutic effect of STS in patients with UP [16].…”
Section: Introductionmentioning
confidence: 99%
“…As in the study being discussed here, no severe side effects were found, provided dialysate sodium had been adjusted to avoid overload. In addition to the two studies cited in the paper, in which, respectively, eighty-six patients were treated for 4 months and twenty-two patients for 5 months, both reporting positive results without relevant side effects, we were able to retrieve three further studies that, albeit with different deigns, reported, once more in the absence of relevant side effects, a positive effect on arterial stiffness (in twenty-four patients randomised for receiving treatment for 5 months [4]), leg pain related with vascular calcifications (18 heavily calcified patients, treated for 6 months [5]), and coronary artery calcifications (17 patients treated for 3 months [6]). In one further study, in which sodium thiosulphate was added to the dialysis fluid, a "positive impression" was reported in six cases [7].…”
mentioning
confidence: 99%
“…A randomized, 6‐month trial of sodium thiosulfate (12.5 gm IV twice weekly) in 50 patients with abnormal arterial stiffness found that the drug significantly reduced the measures of this stiffness and stabilized vascular calcification compared to the control group …”
mentioning
confidence: 99%
“…4 A randomized, 6-month trial of sodium thiosulfate (12.5 gm IV twice weekly) in 50 patients with abnormal arterial stiffness found that the drug significantly reduced the measures of this stiffness and stabilized vascular calcification compared to the control group. 5 Reanalysis of prospective data in 624 HD patients from a nutrition study found that use of a low dialysate potassium concentration (1 mEq/L) in patients with high (≥5 mEq/L) predialysis serum potassium was associated with a 2.9 fold higher mortality than that was seen with a 2 mEq/L bath (HR 0.74); mortality rates were not increased in patients with a lower serum potassium treated with a 1 mEq/L dialysate potassium. A greater dialysate-serum gradient is postulated as the cause.…”
mentioning
confidence: 99%